DUAL-CURING RESIN CEMENT WITH COLOR INDICATOR: CHANGE OF COLOR BY CURING AND SOME PHYSICAL PROPERTIES - Niemi, Aki (My University, 2019)
Objective. To investigate a color indicator containing dual curing resin composite luting cement and to plot the color change to the time of solidification of the cement. In addition some physical properties of the cement were studied after autopolymerization only, and with the light initiated polymerization. Methods. Specimens were made of a dual-cure resin cement (Maxcem Elite Chroma, Kerr, Orange, CA, USA) and polymerized by autopolymerization only, or with light initiated polymerization. A spectrophotometer was used to quantify the color change of the cement as plotted with the curing time. The efficacy of the curing process was studied by measuring water sorption and the ultimate flexural properties of the cement. Results. Flexural strength of cement after autopolymerization was 27.3 MPa (SD=5.1, n=8) and after light initiated polymerization 48.1 MPa (SD=7.5, n=8). Young’s modulus of bending was 2089.3 MPa (SD=586.6, n=8) and 3781.5 MPa (SD=425.3, n=8) respectively for the same cement samples. Water sorption after two weeks for the autopolymerization cement samples was -1.12 wt% (SD=0.75, n=8) and for the light initiated polymerization samples 0.56 wt% (SD=0.20, n=8). Non parametric Spearman’s correlation was measured for autopolymerized cement samples between variables for color and for solidification (load (N)), which showed a strong correlation between curing process and color change (p<0.05). Conclusion. The results of this study showed that there was a correlation between the color change and degree of monomer conversion of the dual curing resin composite luting cement which contained a color indicator system for polymerization reaction. The study also suggested that autopolymerization only resulted in suboptimal polymerization of the cement. By additional light curing considerably higher flexural properties were obtained.